2018
DOI: 10.3390/geriatrics3030045
|View full text |Cite
|
Sign up to set email alerts
|

Illness Representation and Self-Care Ability in Older Adults with Chronic Disease

Abstract: Chronic illness affects >50% of adults in the United States and accounts for >80% of healthcare spending. The purpose of this study was to determine whether beliefs about one’s chronic disease (illness representation) are associated with self-care activation, emergency department (ED) visits, or hospitalizations. Using a cross-sectional design, we recruited older adults with heart failure, chronic obstructive pulmonary disease (COPD), and chronic kidney disease. The Revised Illness Perception Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Both studies found that clusters where patients perceived their pain as having most consequences for their lives had more primary care visits. Riviera et al [ 67 ] identified three clusters based on 187 patients with heart failure, chronic obstructive pulmonary disease (COPD), and chronic kidney disease. The cluster perceiving the illness to have few consequences and a non-fluctuating pattern had the fewest hospitalizations while both the cluster perceiving many consequences to their illness and the cluster perceiving a high disease control and understanding of their illness had many hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies found that clusters where patients perceived their pain as having most consequences for their lives had more primary care visits. Riviera et al [ 67 ] identified three clusters based on 187 patients with heart failure, chronic obstructive pulmonary disease (COPD), and chronic kidney disease. The cluster perceiving the illness to have few consequences and a non-fluctuating pattern had the fewest hospitalizations while both the cluster perceiving many consequences to their illness and the cluster perceiving a high disease control and understanding of their illness had many hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of illness representations is derived from the common-sense model postulating that when facing a health threat, an individual produces illness representations to cope and form strategies, appraises the effectiveness of the strategies, and then adjusts the coping strategies and feedback to evaluate the threat perception (Leventhal et al, 2011). Previous studies have confirmed that illness representations not only are substantially associated with perceived general health in patients with HF (Lerdal, Hofoss, Gay, & Fagermoen, 2019) but also can affect adherence to health-related behaviours, such as following medical plans, participating in dietary modifications (Jones, Smith, & Llewellyn, 2016) and self-care activation (Rivera et al, 2018). However, Albert et al (2014) found that patients with acute decompensated HF had inaccurate HF beliefs and poor self-care adherence in the two weeks before seeking emergency department care.…”
Section: Illness Representations Are Individuals' Perceptions and Belmentioning
confidence: 99%
“…They further suggested the needs for predischarge HF education targeting the improvement of illness representations and self-care behaviours. However, the self-care education should be tailored based on the patient's specific illness representation to make it more meaningful to the patient (Rivera et al, 2018).…”
Section: Illness Representations Are Individuals' Perceptions and Belmentioning
confidence: 99%
“…Further, it leads to patient's gratification, empowering, self-control and improving the whole patient's quality of life. [4,6,7] To improve self-care management among adult and geriatric patients with chronic illness; self-efficacy should be investigated in order to be developed. Self-efficacy is described as the belief of the individual in his/her potentials to accomplish own goals and reach the desired targets.…”
Section: Introductionmentioning
confidence: 99%
“…It is the main and considerable power for assessing and managing chronic health conditions. Further, it is the key to psychological and physiological development which leads to coping with environments and performing healthy behaviors [7,8,9]. Patients with high self-efficacy have an elevated trust in their potentials to do complicated tasks and cope with any disease challenges.…”
Section: Introductionmentioning
confidence: 99%